Bio‐Inspired Two‐Dimensional Nanofluidic Generators Based on a Layered Graphene Hydrogel Membrane. (31st July 2013) - Guo, Wei; Cheng, Chi; Wu, Yanzhe; Jiang, Yanan; Gao, Jun; Li, Dan; Jiang, Lei
<x xml:space="preserve">Abstract</x> An electrogenetic layered graphene hydrogel membrane (GHM) possesses ultra‐large interlayer spacing of about 10 nm, forming charged 2D nanocapillaries between graphene sheets that selectively permeate counter‐ions and exclude co‐ions. When an electrolyte flow goes through the GHM, it functions as an integrated 2D nanofluidic generator converting hydraulic motion into electricity. The maximum streaming conductance density approaches 16.8 μA cm−2 bar−1. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>